Psychological characteristics and associations between living kidney transplantation recipients and biologically related or unrelated donors - Yujin Lee; Hyewon Park; Hee-Jung Jee; Heon-Jeong Lee; Jun Gyo Gwon; Hyeonjin Min; Cheol Woong Jung; Myung-Gyu Kim; Chul-Hyun Cho (BMC Nephrology, 2020)
Abstract Background Although recipients and donors in living kidney transplantation experience psychological distress—including depression and anxiety—during the pre-operative period, very few studies have evaluated the related psychological reactions. This study aimed to determine the characteristics and correlations of the mood states and personality of recipients and donors (genetically related and unrelated) of living kidney transplantations. Methods A total of 66 pairs of living donors and recipients were enrolled from April 2008 to June 2019 in this study, of whom 53 eligible pairs of living donors and recipients were included in the retrospective analysis of their psychological assessments in the pre-transplantation states. While participants’ personality patterns were assessed using the Minnesota Multiphasic Personality Inventory-2 (MMPI-2), mood states were evaluated via both the State-Trait Anxiety Inventory (STAI) and The Center for Epidemiologic Studies Depression Scale (CES-D). Statistical analysis was performed using paired t-tests and Spearman’s correlation analyses. Results The recipient group showed significantly higher scores for Hypochondriasis (t = − 4.49, p = .0001), Depression (t = − 3.36, p = .0015), and Hysteria (t = − 3.30, p = .0018) of MMPI-2 and CES-D (t = − 3.93, p = .0003) than the donor group. The biologically unrelated recipient group reported higher scores of Hypochondriasis (t = − 3.37, p = .003) and Depression (t = − 2.86, p = 0.0098) than the unrelated donor group. Higher scores for Hypochondriasis (t = − 3.00, p = 0.0054) and CES-D (t = − 3.53, p = .0014) were found in the related recipient group. A positive association was found for Hypomania (r = .40, p = .003) of MMPI-2, STAI-S (r = .36, p = .009), and CES-D (r = .36, p = .008) between the recipient and donor groups. Conclusions Recipients suffered from a higher level of depression and somatic concerns than donors before living kidney transplantation. Psychological problems like depression and anxiety can occur in both living kidney transplantation donors and recipients. This study suggests that clinicians must pay attention to mood states not only in recipients but also in donors because of emotional contagion.